Determination of Chromium in Tannery Effluent and Study of Adsorption of Cr (VI) on Saw dust and Charcoal from Sugarcane Bagasses - Dhungana, T. P.; Yadav, P. N. (Journal of Nepal Chemical Society, 2009)
Spectrophotometric method using diphenylcarbazide as a colour developing reagent has been used to analyze the chromium content in tannery effluent located in Bara and Parsa districts of Nepal and Sirsiya River which is an ultimate drainage of these waste water streams. The adsorption of hexavalent chromium from aqueous solution onto formaldehyde treated sawdust and charcoal of sugarcane begasses has been investigated at various Cr(VI) concentrations of 5-40 mg/L and pH values. From the experimental observations, it has been found that chromium can be removed quantitatively at the equilibrium pH range of around 1 and the adsorption behavior revealed to follow Langmuir and Freundlich adsorption isotherms. Keywords : chromium, diphenylcarbazide, adsorption. DOI: 10.3126/jncs.v23i0.2102 Journal of Nepal Chemical Society, Vol. 23, 2008/2009 Page; 93-101